1996
DOI: 10.1063/1.363586
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the optical dielectric function of GaAs and AlAs: Extension of Adachi’s model

Abstract: Optical dielectric function model of Ozaki and Adachi ͓J. Appl. Phys. 78, 3380 ͑1995͔͒ is augmented by introducing Gaussian-like broadening function instead of Lorentzian broadening. In this way a consistent and comparatively simple analytic formula has been obtained, which accurately describes the optical dielectric function of GaAs and AlAs in a wide spectral range between 0.1 and 6 eV. The acceptance-probability-controlled simulated annealing technique was used to fit the model to experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 43 publications
(56 reference statements)
3
74
0
Order By: Relevance
“…Various theoretical models have, therefore, been proposed recently which enable calculation of the optical constants in the interband-transition region of alloy semiconductors. [17][18][19][20][21][22] The purpose of this article is to present the optical constants of cubic Cd x Zn 1Ϫx Se ternary alloys. The calculation model used in this study is based on a simplified model of the interband transitions, named the model dielectric function ͑MDF͒.…”
Section: Introductionmentioning
confidence: 99%
“…Various theoretical models have, therefore, been proposed recently which enable calculation of the optical constants in the interband-transition region of alloy semiconductors. [17][18][19][20][21][22] The purpose of this article is to present the optical constants of cubic Cd x Zn 1Ϫx Se ternary alloys. The calculation model used in this study is based on a simplified model of the interband transitions, named the model dielectric function ͑MDF͒.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that by replacing the damping constant J with the frequency dependent expression, better agreement with experimental data can be achieved for both models of Kim et al [23] and of Adachi [24] for the zmcblende semiconductors. Therefore, in the model for hexagonal semiconductors employed here we replace damping constants 17 (j = 0.…”
Section: Description Of the Modelmentioning
confidence: 94%
“…The fact that Lorentzian broadening fails to describe accurately absorption processes, especially in E0 critical point region, has already been recognized [23][24][25][26]. It was shown that by replacing the damping constant J with the frequency dependent expression, better agreement with experimental data can be achieved for both models of Kim et al [23] and of Adachi [24] for the zmcblende semiconductors.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The dielectric function in the Adachi model is represented by the sum of terms describing the transitions at the critical points in the joint density of states. In the modification proposed by Rakić and Majewski, 23 damping constants ⌫ i are replaced with the frequency-dependent ex-…”
Section: Model Of the Dielectric Functionmentioning
confidence: 99%
“…The fact that Lorentzian broadening does not describe the optical spectrum accurately has already been recognized and discussed by several groups. [20][21][22][23] Rakić and Majewski 23 have shown that the Adachi model, with a Gaussian-like broadening function, can describe accurately the dispersion and absorption of GaAs and AlAs even in the vicinity of the E 0 , where the original model of Ozaki and Adachi 9 is highly inaccurate. In this work, we use a similar model, which considers the contribution of exitonic terms only at E 0 , E 0 ϩ⌬ 0 CPs, since the excitonic effects are usually more pronounced at E 0 than at any other CPs.…”
Section: Introductionmentioning
confidence: 99%